Profil Agresivitas Siswa Sma Muhammadiyah Berau - Kuriawan, Maulana Ichsan; Prasetya, Akhmad Fajar (CV. SINAR HOWUHOWU, 2025)
This study aims to describe the level of aggressiveness among students of SMA Muhammadiyah Berau and its implications for the development of a comprehensive Guidance and Counseling (GC) program. The research employed a quantitative approach with a survey design. The instrument used was an aggressiveness scale adapted from the Aggression Questionnaire developed by Buss and Perry. Convenience sampling was applied, involving 35 student respondents. Data were analyzed using descriptive statistics based on the mean, while validity and reliability testing were conducted using SPSS Statistics version 20. The results indicate that the majority of students (94%) fall into the low aggressiveness category, while 6% are categorized as having moderate aggressiveness, and no students were identified with high aggressiveness. These findings suggest that a conducive school climate and character education grounded in Islamic progressive values contribute positively to students’ ability to control aggressive behavior. From a comprehensive Guidance and Counseling perspective, the findings emphasize the importance of strengthening basic services as preventive efforts, providing responsive services for students with moderate aggressiveness, and enhancing system support through collaboration among counselors, subject teachers, homeroom teachers, and parents. The aggressiveness profile obtained from this study can serve as a foundation for planning and developing sustainable and needs-based comprehensive Guidance and Counseling services.